Seismic Response Analysis along the Coastal Area of Bengkulu during the September 2007 Earthquake - Mase, Lindung Zalbuin (Makara Journal of Technology, 2018)
A strong earthquake of 8.4 Mw occurred at the Sumatra Subduction Zone in September 12, 2007. The area that underwent the impact of the earthquake was located along the coastal area of the Bengkulu Province. A seismic ground response study was then performed with reference to the event. Several site investigations, including standard penetration test and shear wave velocity tests, were conducted to understand the subsoil condition. The data were used to analyze a ground response during the earthquake. The amplification factor of each site was obtained, and a comparison of the spectral accelerations was performed. The results showed that the study area could undergo an amplification factor ranging from 1.1 to 1.5 during the seismic wave propagation. The spectral acceleration that resulted from the seismic response analysis was also within the design value. The study results could generally bring awareness to local engineers to consider the seismic design value for the coastal area of the Bengkulu Province, particularly if a stronger earthquake happens in the future.